Perils and Promises of Pathogenic Protozoan Extracellular Vesicles - Olajide, Joshua Seun; Cai, Jianping (Frontiers in Cellular and Infection Microbiology, 2020)
Extracellular vesicles (EVs) are membranous structures formed during biological processes in living organisms. EVs secreted by protozoan parasites during face-off with stressors, in the hosts and in cultures, characteristically reflect the biochemical features of their parasitic origin and activating stimuli. Experientially, studies on EVs produced by protozoan parasite-infected host cells have been relatively reviewed. Meanwhile, investigations on EVs secreted directly by protozoan parasite are on the rise. Here is conspectus of pathogenic protozoan EVs (PPEVs) with focus on species-specific morphology and integrity in concurrence with origin, functions and internalization process by recipient cells. The activating stimuli are discussed alongside exports and functions of protozoan parasites EVs bioactive molecules in relation to the consequent responses of immune cells. In finale, we highlight some areas that deserve further investigations